Correction: El-Sawah et al. Arbuscular Mycorrhizal Fungi and Plant Growth-Promoting Rhizobacteria Enhance Soil Key Enzymes, Plant Growth, Seed Yield, and Qualitative Attributes of Guar. Agriculture 2021, 11, 194 - Ahmed M. El-Sawah; Ali El-Keblawy; Dina Fathi Ismail Ali; Heba M. Ibrahim; Mohamed A. El-Sheikh; Anket Sharma; Yousef Alhaj Hamoud; Hiba Shaghaleh; Marian Brestic; Milan Skalicky; You-Cai Xiong; Mohamed S. Sheteiwy (Agriculture, 2021)
In the original article [...]